Assessing pragmatics in early childhood with the Language Use Inventory across seven languages - Pesco, Diane; O’Neill, Daniela K. (Frontiers in Psychology, 2023)
The Language Use Inventory (LUI) is a parent-report measure of the pragmatic functions of young children’s language, standardized and norm-referenced in English (Canada) for children aged 18–47 months. The unique focus of the LUI, along with its appeal to parents, reliability and validity, and usefulness in both research and clinical contexts has prompted research teams globally to translate and adapt it to other languages. In this review, we describe the original LUI’s key features and report on processes used by seven different research teams to translate and adapt it to Arabic, French, Italian, Mandarin, Norwegian, Polish, and Portuguese. We also review data from the studies of the seven translated versions, which indicate that all the LUI versions were reliable and sensitive to developmental changes. The review demonstrates that the LUI, informed by a social-cognitive and functional approach to language development, captures growth in children’s language use across a range of linguistic and cultural contexts, and as such, can serve as a valuable tool for clinical and research purposes.